The manner of the Prophet – concealed, found and regained: Revisiting the science of women. Issue 132 (4th May 2017) - Braginsky, Vladimir
ABSTRACT: This article continues an earlier investigation in this journal (2004), of the synthesis of Sufism and Tantrism in a corpus of texts from Aceh between the 16th and 19th centuries. The revisiting was stimulated by a rapid development of scholarship on the interaction of Sufism and Tantra/yoga in the Islamic oikoumene and the discovery of new, more detailed texts in Malay on this subject. The most important among them is Bustān al-sālikīn ( Garden of wayfarers); found in the MS PNI Jakarta Ml. 110 (ff.2v–30r). A loosely structured themed anthology, Bustan consists of ten chapters that contain treatises providing a comprehensive idea of the Sufi-Tantric branch of Islamic mysticism in Aceh and, mutatis mutandis, in the Malay-Indonesian world. Although summarising the entire Bustan, the article concentrates on ilm al-nisa ( 'ilm al-nisā'; the science of women) from the text's early chapters and examines it within the context of the Acehnese Sufi-Tantric corpus and Sufi-yogic/Tantric works of the Islamic world. The author of Bustan made every effort to legitimise the science of women as a genuinely Islamic doctrine of spiritual wedding with unio mystica as its final goal. Allegedly created and practised by the Prophet Muḥammad himself, ilm al-nisa includes the practices of mystical gazing, breathing, touching and coition. The article scrutinises their Sufi and Tantric aspects, revealing the synthesis underpinning them. Against the background of early forms of Islam in the Malay-Indonesian world, this synthesis, by facilitating the mutual 'translatability' of the old and the new religion, was instrumental in the peaceful Islamisation of the region.